Multifractal analysis of the dynamics of NIKKEI and HKSE Asian stock indices - Ляшенко, Олена Ігорівна; Крицун, Катерина Ігорівна (Technology audit and production reserves, 2016)
The paper studies the dynamics of NIKKEI and HKSE stock indices in Asia from 2014 to 2015. The work uses multifractal analysis and R/S analysis to study the dynamics of the stock indices. The research reviews scientific works that has multifractal analysis as the subject of research. The study highlights the calculation of Hurst coefficient using Gretl and reveals the presence of memory in the time series. The research shows that time series has multifractal properties detected by SpectrAnalyzer. The paper graphically draws the characteristics of time series such as the multifractal singularity spectrum and dynamics of the fluctuation functions. The authors describe further plans in their study of financial indicators.